Analysis of liquid extracts from tree and grass pollens by capillary electromigration methods - Sázelová, Petra; Kasicka, Václav; Koval, Dusan; Peltre, Gabriel (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2004)
Capillary electromigration methods, zone electrophoresis (CZE), micellar electrokinetic chromatography (CMEKC) and isotachophoresis (CITP), have been used for analysis of water and water-buffer extracts from tree-common birch (Betula verrucosa) and grass-orchardgrass (Dactylis glomerata) pollen samples. Water extracts were analyzed by CZE using acetic acid as background electrolyte (BGE), by CMEKC in tris-phosphate BGE with anionic detergent sodium dodecyl sulfate (SDS) micellar pseudophase (TP-SDS) and by CITP in cationic mode with leading/terminating cations K+/BALA+ (beta-alanine (BALA)) and in anionic mode with leading/terminating anions Cl-/MES- (2-(N-morpholino)ethanesulphonic acid (MES)). Moreover, acetic acid extracts were analyzed by CZE using acetic acid as BGE, and alkaline water-SDS-buffer extracts were analyzed by CMEKC using TP-SDS as BGE. Extracted amounts of pollen allergens and other UV-absorbing compounds and the number of resolved components were evaluated from CZE, CMEKC and CITP analyses of the liquid extracts. Larger amounts of UV-absorbing material were found in the water-buffer pollen extracts than in the water extracts. More UV-absorbing material was found in all extracts from D. glomerata pollen than in relevant extracts from B. verrucosa pollen. It was found by CITP that the extracted amounts of anionic components and their number were much higher than those of cationic components. Concentrations of some inorganic ions (e.g. Cl-, K+, Na+, Ca2+) in pollen samples were also determined by CITP.
Keywords: stromy; Poaceae; chromatografie micelární elektrokinetická kapilární; Trees; Electrophoresis, Capillary; lipnicovité; elektroforéza kapilární; Chromatography, Micellar Electrokinetic Capillary